Existential Threat: Uncovering Implicit Affect in Response to Terror Reminders in Soldiers - Quirin, Markus; Malekzad, Farhood; Kazén, Miguel; Luckey, Udo; Kehr, Hugo (Frontiers in Psychology, 2021)
Psychological science has a hard time assessing individuals’ affective processes that they may not recognize or do not like to report on. Here we used the Implicit Positive and Negative Affect Test (IPANAT; Quirin, Kazén, Kuhl, 2009) to investigate whether reminders of an existential threat induce unpleasant implicit affect in soldiers waiting for their deployment to a country with high levels of terrorist threat, Afghanistan. As expected, relative to reminding participants of a television evening, implicit negative affect was higher and implicit positive affect was lower after reminding participants of terror acts performed in different cities. No significant effects were found in self-reports of negative or positive affect. Our findings suggest that reminders of existential threat can elicit implicit negative affect that individuals may not report on explicitly, and thus validate the IPANAT as an easily applicable measure in emotional contexts.